Structural performance of hybrid sandwich slabs under shear loading - Mastali, Mohammad (2019)
In a hybrid panel with glass fiber reinforced polymer (GFRP) bottom skin and ribs, and deflection hardening cementitious composites (DHCC) top layer, it is very important to provide good shear connection between these various components in order to increase the load carrying capacity of the resulting hybrid slabs and a larger increment of deflection before the occurrence of the structural softening of this panel. The effectiveness of the proposed hybrid sandwich panels strongly depends on the performance of the shear connectors. The efficiency of indented shear connectors in improving the flexural performance of hybrid sandwich panels is here demonstrated. Since the efficiency of indented shear connectors in the hybrid sandwich panels is unknown, efforts are made in this paper in investigating the shear performance of hybrid slabs. A special focus is given on the indented shear connector’s behavior, considering different shear span ratios in ranges of 2.00, 1.39, and 0.77. In this regard, six hybrid sandwich panels were manufactured and experimentally tested under different shear loads. Then, the results are interpreted comprehensively. The results obtained show that the GFRP rib thickness and height, and shear span ratios influence the damage events and the structural performance of the hybrid sandwich panels. Moreover, it was observed that using indented shear connectors in the hybrid slabs, regardless of the shear span ratios, provides high load capacity, high stiffness, and large residual deflection.